The Oceanic Vision of Sugimoto Hiroshi. Issue 2 (2nd April 2016) - Petitto, Joshua
Abstract : The artistic imagination of Sugimoto Hiroshi revolves around images of the oceanic intended, in their presentation of flat, open, and tranquil calm, to counter the forces of modernity and restore a sense of the religious in the profane. Sugimoto's oceanic vision, however, also draws upon elements of a politically regressive ideology that marked Japanese cultural productions in the 1930s which bound the hope of restoration to an aesthetics of death and repose. In this article, I illustrate how Sugimoto's oceanic vision disturbs this ideology even as it invokes the visual and rhetorical structures that marked its forms.